PENGARUH TINGKAT LITERASI MEDIA ORANG TUA TERHADAP PENGAWASAN PENGGUNAAN YOUTUBE PADA ANAK USIA SEKOLAH (Survey pada Orang Tua di Kelurahan Jatimelati, Bekasi) - Ammar Syakira Wahid, (2022)
This study aims to determine the effect of parents' level of media literacy on monitoring the content their children watch on YouTube and to raise awareness of parents in using and utilizing YouTube in order to provide control over the content watched by children. The approach used in this research is a quantitative approach with the type of explanatory research. The paradigm uses a positivistic paradigm which is identical to research with a quantitative approach. Sampling technique used was probability sampling with purposive sampling. Researchers used a survey method to collect data by distributing questionnaires to the sample. Sconul 7 Pillars model of information literacy is used as a dimension base. The final result of this study shows that there is a significant relationship between the media literacy level of parents and the supervision of YouTube of school-age children. The correlation coefficient value is 0.622 where in the Spearman Rank table is categorized as strong category. It is also known that the effect of media literacy levels on monitoring the use of YouTube is 33.7%. This is in line with the theory of media ecology where society cannot be separated from the influence of technology.